2013
DOI: 10.1038/ctg.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Viral and Microbial Communities Associated With Crohn's Disease: A Metagenomic Approach

Abstract: OBJECTIVES:This study aimed to analyze and compare the diversity and structure of the viral and microbial communities in fecal samples from a control group of healthy volunteers and from patients affected by Crohn's disease (CD).METHODS:Healthy adult controls (n=8) and patients affected by ileocolic CD (n=11) were examined for the viral and microbial communities in their feces and, in one additional case, in the intestinal tissue. Using two different approaches, we compared the viral and microbial communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 62 publications
6
103
0
Order By: Relevance
“…The possibility of using phages as viral biomarkers has potential. One study found among the viral biomarkers identified, 5 % were more represented in CD patients than in healthy controls [115]. A recent publication confirms increased richness and biodiversity of phage populations in IBD patients compared with controls [116].…”
Section: The Gut Virome and Ibdmentioning
confidence: 95%
“…The possibility of using phages as viral biomarkers has potential. One study found among the viral biomarkers identified, 5 % were more represented in CD patients than in healthy controls [115]. A recent publication confirms increased richness and biodiversity of phage populations in IBD patients compared with controls [116].…”
Section: The Gut Virome and Ibdmentioning
confidence: 95%
“…Similar to fungi, only a few studies have been published examining the populations of viruses in patients with IBD. CD patients may harbor increased numbers of bacteriophages in inflamed tissue and feces, though no specific viruses have been associated with human IBDs to date [9,10]. …”
Section: Inflammatory Bowel Diseases Are Associated With Altered Gut mentioning
confidence: 99%
“…ples from CD patients compared with healthy subjects (45). The functional significance of these findings remains unknown, due to the lack of reference genome inventories needed for identification and functional classification of bacteriophages.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%